Pengaruh Pengungkapan Corporate Social Responsibility, Good Corporate Governance, dan Kinerja Keuangan Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Periode 2017-2019) - Nadya Eka Sri Mukhita; Tatas Ridho Nugroho; Nur Nur Ainiyah (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2022)
Disclosure of Corporate Social Responcibility and implementation of Good Corporte Governance are needed by companies to improv financial performance. High financial performance has a good effect on the value of the company. The company must be able to increace the value of its company so that investors believe and invest in the company. This research aims to find out the effect of corporate social responsibility disclosure, good corporate governance, and financial performance on the value of the company. The data used in this study was otained from the data of the annual report of mining companie listed on the Indonesia Stock Exchange for the period 2017-2019. The sampling method used is purposiv sampling. The number of samples used in the study was as many as 20 companies. The technical data analysis used is partial least square analysis. The results of this study show that the corporate social responsibility variable had no effect on the company's value, good corporate governance had no efect on the company's value, and financial performance had no effect on the company's value.